2020
DOI: 10.1111/are.14761
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyl diselenide‐loaded nanocapsules in silver catfish feed enhance growth, improve muscle antioxidant/oxidant status and increase selenium deposition: Advantages of nanotechnology for fish health

Abstract: The aim of this study was to determine whether feed supplementation with nanoencapsulated Ph2Se2 would improve the growth performance of silver catfish and would maintain or improve the muscle antioxidant system. Final mean weight (p = .031), weight gain (p = .014) and specific growth rates (p = .045) were significantly higher in supplemented fish than in the control group. Muscle reactive oxygen species (p = .0001) levels were significantly lower in supplemented fish than in the control group. Also, muscle hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Moreover, organic Se supplementation (up to 0.3 mg kg -1 d.w. of diet) showed significant improvement in feed utilization and growth performance of African catfish ( Clarias gariepinus ) [ 50 ]. Another recent study by Baldissera et al [ 51 ] demonstrated that silver catfish ( Schilbe mystus ) fed with nanoencapsulated selenium (diphenyl diselenide-loaded nanocapsules) had significant improvement in growth performance compared to the control group in addition to improvement in antioxidant/oxidant status. Furthermore, a previous study by Zhou et al [ 31 ] demonstrated that dietary Se nanoparticles significantly improved final weight and Se concentration in muscle of crucian carp ( Carassius auratus gibelio ) compared to Se-Met.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, organic Se supplementation (up to 0.3 mg kg -1 d.w. of diet) showed significant improvement in feed utilization and growth performance of African catfish ( Clarias gariepinus ) [ 50 ]. Another recent study by Baldissera et al [ 51 ] demonstrated that silver catfish ( Schilbe mystus ) fed with nanoencapsulated selenium (diphenyl diselenide-loaded nanocapsules) had significant improvement in growth performance compared to the control group in addition to improvement in antioxidant/oxidant status. Furthermore, a previous study by Zhou et al [ 31 ] demonstrated that dietary Se nanoparticles significantly improved final weight and Se concentration in muscle of crucian carp ( Carassius auratus gibelio ) compared to Se-Met.…”
Section: Resultsmentioning
confidence: 99%
“…The selenium supplementation in the diet has been related with beneficial effects that increase the aquaculture potential of fish species (Zheng et al 2018 ); therefore, diphenyl diselenide was effective to increase basal antioxidant tonus in tissues of silver catfish (Menezes et al 2016 ). When nanocapsules were applied as carriers of diphenyl diselenide in the diet, an improvement in the muscle antioxidant capacity and growth performance of silver catfish were reported (Baldissera et al 2020a , b , c , d ) (Table 8 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“…Furthermore, dietary supplementation of Se‐NPs encapsulated form (diphenyl diselenide‐loaded nanocapsules) improved the growth and antioxidant status of silver catfish ( Schilbe mystus ) 73 . When combined with vitamin C (300 mg/kg), dietary Se‐NPs supplementation (0.68 mg/kg) showed synergistic interactions that positively enhanced weight gain, specific growth rate and feed conversion efficiency in mahseer fish ( Tor putitora ) 74 …”
Section: Applications Of Inorganic Nps In Aquaculturementioning
confidence: 99%